'Little flat furnished by Maple . . . ' The 'English Taste' in Buenos Aires: The Thompson and Maple Companies (1887–1986). (19th March 2016) - Fernández-García, Ana María
Abstract : In the last decades of the nineteenth century, several companies established themselves in Buenos Aires to sell furniture and decorative objects coming from the United Kingdom. This paper offers a brief history of the two most representative importing companies: the Thompson Company, and the branch of the Maple Furniture Company in the capital of Argentina. These two companies, which were closely related and had developed a tense commercial relationship, were the main reason for the consolidation of English taste in Buenos Aires. Combining direct imports from the UK with their own production, they both developed a very active decorating business for private homes, public places and official institutions. Although closely involved with the British population in the country, they also worked for a wide range of clients of the 'criollo' or creole and immigrant sector. They became so prestigious, and enjoyed such a high profile, that even today the lyrics of the famous tango 'Y todo a media luz' can still remind us of their importance.